Implementation of Participatory Development in Tarung-Tarung Nagari, Rao District, Pasaman Regency - Midun Midun; Junaidi Indrawadi (PERSPEKTIF, 2022)
This article aims to analyze the implementation of participatory development in Nagari Tarung-Tarung, Rao District, Pasaman Regency. The problem is focused on participatory development. The data were collected by means of observation, interviews, Focus Group Discussion (FGD), and documentation and analyzed qualitatively. This study concludes that: The implementation of participatory development in Nagari Tarung-Tarung, Rao District, Pasaman Regency consists of three components: (a) Planning, (b) implementation, and (c) evaluation/monitoring. In these three stages, development is focused on building physical infrastructure, such as road construction, irrigation development, and road paving. However, what is planned is often not on target in implementation, so that community participation in Nagari development is not good due to the lack of public trust in the government, so that planning the Musrenbang until the implementation stage is not achieving the target, as well as the Nagari government in the implementation of development does not pay attention to the aspirations of the community by meeting mutual attitudes. believe. Only a part of the community gave aspirations. This means that community support for development in Nagari Tarung-Tarung is very small, this is marked by the lack of transparency from the Nagari government so that people are not so enthusiastic about development, there is an impression of apathy and leave everything to the government.